Analisis Retorika Pada Akun Instagram @jrxsid - Anugrah, Achirul Satriya; Evita, Jeanette Maria (Fakultas Ilmu Komunikasi Universitas Bhayangkara Jakarta Raya, 2021)
The presence of people who are quite potential as influencers can certainly have an effect in providing an impact or information that will immediately spread to the community. Some of them are equipped with good rhetoric skills. Rhetoric itself is the ability to persuade someone through a given message or gesture, one of which is in the form of a campaign. The ability to rhetoric itself is important for a communicator to do so that messages or information can be conveyed properly to the audience. Likewise what happened to a member of the band SID (Superman Is Dead), who recently became a conversation because of his actions that spread messages through his personal Instagram account. Many responses came from internet users, both pros and cons. Jerinx, or whose real name is I Gede Ari Astina, once uploaded his statement regarding a case related to a pandemic which certainly caused a commotion to the public. However, not a few of them thought hard about Jerinx's opinion, who said that